Money Politic dalam Pemerintahan Desa di Indonesia - Sitorus, Nurqowwiyani Zulnun; Aprilia, Erika; Tanjung, Elsa Susanna Fitri; Sinurat, Patricia; Simanjuntak, March Kevin; Handika, Putra; Sitinjak, Ryan Fernando (Journal of Law & Policy Review, 2023)
This article or article aims to see whether the practice of money politics finds changes in the implementation of village governance in Indonesia. As it is known, the practice of money politics that occurs in the government in our country, both from the village and national levels, can injure the democracy of the Indonesian nation and harm the people. This research discusses how the practice of money politics (Money Politics) in village government in Indonesia. The data were collected through tracing the literature study and analyzed qualitatively. This study concludes that the implications of money politics cause the destruction of all levels of society from the highest to the lowest levels. This shows that the consequences of these things have a significant impact on the sustainability of the world of politics and the culture of democracy in Indonesia so that it is necessary to take quick and responsive steps both from the government as a venue for money politics with the community as the manipulated and used party.